Beware, the snowman - Stine, R. L. (New York : Scholastic, 1997)
Jaclyn cannot figure out why her Aunt Greta moved them to the tiny Arctic village of Sherpia where the townspeople are all living in fear of the Snowman, an evil creature that lives in an ice cave on top of a nearby mountain, but then she learns a secret that changes her life.
2.8
5-8
Keywords: Good and evil -- Juvenile fiction; Monsters -- Juvenile fiction; Snowmen -- Juvenile fiction; Good and evil -- Fiction; Horror stories; Monsters -- Fiction; Snowmen -- Fiction; Good and evil -- Fiction; Horror fiction; Monsters -- Fiction; Snowmen -- Fiction; Horror fiction